English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-30 20:43:09 · 2 answers · asked by Kelvin K 2 in Science & Mathematics Mathematics

2 answers

y = ce^(y/x)
ln y = ln (ce^(y/x))
ln y = ln c + ln e^(y/x)
ln y = ln c + (y/x)
Differentiate both side d/dx
(1/y)(dy/dx) = 0 + (dy/dx)(1/x) - y/x^2
(dy/dx)(1/y - 1/x) = -y/x^2
(dy/dx)((x-y)/xy) = -y/x^2
dy/dx = y' = (-y^2)/(x(x-y))

2007-01-30 21:07:50 · answer #1 · answered by seah 7 · 1 0

y= c.e^(y/x)
dy/dx = {c.[x(dy/dx) - y].e^(y/x)} / (x^2)

use the chain rule and evaluate the derivative of (y/x) using the quotient rule.
Hope this helps!

2007-01-31 05:37:34 · answer #2 · answered by yasiru89 6 · 0 0

fedest.com, questions and answers